Severity Assessment of Problems in Turkish Building Audit System: A Fuzzy AHP Approach - Cevikbas, Murat; Okudan, Ozan; Isik, Zeynep (TURKISH CHAMBER CIVIL ENGINEERS, 2023)
The Building Audit system (BAS) has often been criticized due to its various drawbacks by researchers, construction practitioners, and professional chambers. Existing studies, however, do not comprehensively investigate the problems seen in Turkish BAS. Since the decision-makers are provided with little knowledge about the drawbacks of the system, they can barely develop new strategies to improve its effectiveness and efficiency. To bridge this gap, this study aimed to identify the drawbacks seen in the implementation of the Turkish Building Audit System (BAS). In addition, the severity of each drawback was also determined to further provide comprehensive guidance to policymakers and nongovernmental organizations (NGOs). Initially, an extensive literature review was conducted to identify problems of Turkish BAS. Identified problems were then validated through Focus Group Discussion (FGD) sessions with the participation of 12 experts who have diverse experience in the related field. Later, a questionnaire survey was designed to measure the severity of each problem/drawback and the data was collected from 15 construction practitioners. The data were then analysed using the Fuzzy Analytical Hierarchy Process (FAHP) method to measure the severities of problems seen in Turkish BAS. Then, the problems were prioritized based on their severities. At the final step, sensitivity analysis was conducted to measure the robustness and reliability of the results derived from the FAHP method. Results revealed that problems such as Lack of practical knowledge of technical staff , Absence of site supervisor at the site Political pressure and Neglecting technical specifications and procedures were determined as the most severe problems that need urgent attention of decision-makers. It is highly believed that this study will guide decision-makers for the improvement of existing legislation. Additionally, it is also believed that practitioners will take necessary precautions beforehand by using the outputs of this study.
Keywords: Building audit system; quality control; quality assurance; construction; FOCUS GROUP; VIKOR; MANAGEMENT; FRAMEWORK; DESIGN; Engineering